Integrated Health Care for Sick Toddlers: A Community Approach to Improving Child Health - Ghita, Dwi; Yuliandini, Astri; Nurhidaya, Nurhidaya (Journal of Evidence-Based Community Health, 2025)
Toddlers as a vulnerable group, experience rapid physical growth and cognitive development. This process is influenced by various factors such as nutritional intake, stimulation and health monitoring which play a significant role in determining the quality of child development in the future. The purpose of this community service activity is to increase the knowledge of mothers as companions for toddlers in their growth and development process. This activity was carried out in the working area of ​​the Binanga Health Center, Mamuju City, West Sulawesi. The method of the activity carried out was a 30-minute counseling session presented by 2 presenters on caring for sick toddlers. The activity was carried out on December 16, 2024 and was attended by 20 counseling participants. The results of this activity showed that mothers understood and were able to independently manage care for sick toddlers at home.